Educational practices of nursing in the puerperium: social representations of puerperal mothers - Hilana Dayana Dodou; Tamires Daianny Araújo de Oliveira; Mônica Oliveira Batista Oriá; Dafne Paiva Rodrigues; Patrícia Neyva da Costa Pinheiro; Izaildo Tavares Luna
ABSTRACT Objective: To understand the social representations of puerperal women regarding the contents of the educational practices carried out by nursing in the puerperium. Method: Descriptive and qualitative study, carried out from June to September 2014, in Fortaleza, Ceará State, Brazil. Nineteen puerperal women were administered a semi-structured interview. The Theory of Social Representations was used as a theoretical reference. Lexical analysis was performed with ALCESTE (version 2012) software. Results: The contents of the representations on educational practice were associated to the nursing team's orientations, with emphasis on breastfeeding and nursing. A lack of educational action regarding self-care of the puerperal woman was also revealed. Final considerations: It is necessary to redirect educational practices in the puerperium, in order to cover the biopsychosocial needs of women in this period of life. The educational actions should be based on the problematizing model, with a stimulus for the autonomy of puerperal mothers and valorization of their social knowledge.